The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2001
DOI: 10.1016/s0014-5793(01)02393-6
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of inducible cyclooxygenase and nitric oxide synthase through activation of peroxisome proliferator‐activated receptor‐γ by flavonoids in mouse macrophages

Abstract: Peroxisome proliferator-activated receptor (PPAR)Q Q transcription factor has been implicated in anti-inflammatory response. Of the compounds tested, apigenin, chrysin, and kaempferol significantly stimulated PPARQ Q transcriptional activity in a transient reporter assay. In addition, these three flavonoids strongly enhanced the inhibition of inducible cyclooxygenase and inducible nitric oxide synthase promoter activities in lipopolysaccharide-activated macrophages which contain the PPARQ Q expression plasmids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
136
2
4

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 208 publications
(152 citation statements)
references
References 41 publications
10
136
2
4
Order By: Relevance
“…28) Our previous study has also demonstrated that several flavonoids were able to activate PPAR and result in decreased inflammation by a transient transfection assay on mouse macrophages. 24) Several studies 31) have further found that a compound of Momordica charantia, 9c, 11t, 13t-conjugated linolenic acid, was the active compound in wild bitter gourd and acted as a PPAR agonist. In the first 6 weeks of our study, the rats were provided with food and water ad libitum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28) Our previous study has also demonstrated that several flavonoids were able to activate PPAR and result in decreased inflammation by a transient transfection assay on mouse macrophages. 24) Several studies 31) have further found that a compound of Momordica charantia, 9c, 11t, 13t-conjugated linolenic acid, was the active compound in wild bitter gourd and acted as a PPAR agonist. In the first 6 weeks of our study, the rats were provided with food and water ad libitum.…”
Section: Discussionmentioning
confidence: 99%
“…After 48 h of incubation, the cells were treated with various extracts of the wild fruiting body of T. camphoratus for 18 h. A total cell lysate was used to determine the luciferase activity with the Dual-Luciferase Reporter Assay kit (Promega) as described previously. 24) Animals and treatments. Male Sprague-Dawley (SD) rats (6 weeks old) were purchased from the National Laboratory Animal Center (Taipei, Taiwan), housed in stainless steel wire-bottomed cages, and acclimatized under laboratory conditions (19-23 C, 60% humidity, 12-h light/dark cycle) throughout the experimental period.…”
Section: Methodsmentioning
confidence: 99%
“…Liang et al found that a higher concentration (IC 50 was 50 μM) was needed to bind to a Gst-PPARγ in an in vitro competitive binding assay, indicating flavonoids might not bind directly to PPARγ (82). Liang et al also found a cytotoxic effect at 20 μM of apigenin in RAW264.7 cells and a corresponding decrease in PPARγ activation (82). Quercetin, a known LOX inhibitor, was found to block keratinocyte differentiation and directly inhibit PPARs and the expression of PPAR-regulated genes (83).…”
Section: Inflammation-sincementioning
confidence: 96%
“…One PPAR sub-family, PPARγ, is thought to be involved with immune response, specifically by activating arachidonic acid metabolites (82). PPARs serve as a link between pro-inflammatory cytokines and gene transcription factors and can influence cellular differentiation, apoptosis, and inflammation (66).…”
Section: Inflammation-sincementioning
confidence: 99%
See 1 more Smart Citation